Alcohol extracts of Chinese bayberry branch induce S‐phase arrest and apoptosis in HepG2 cells. Issue 1 (2nd October 2022) - Zheng, Yuanyuan; Yu, Zheping; Li, Yougui; Zhong, Shi; Sun, Yuqing; Sun, Li; Zheng, Xiliang; Qi, Xingjiang; Zhang, Shuwen
Abstract: The alcohol extracts of Chinese bayberry ( Myrica rubra ) branches (MRBE) are rich in flavonoids which have a variety of medicinal benefits, but their effects on human HepG2 were unknown. In this study, the effects of MRBE on HepG2 cell growth and its potential for inhibiting cancer were explored. The results displayed that MRBE inhibited HepG2 proliferation both by arresting cells in S phase and promoting apoptosis. Quantitative reverse‐transcription PCR (qRT‐PCR), western blotting, and immunofluorescence showed that MRBE induced S‐phase arrest by upregulating p21, which in turn downregulated cyclin and cyclin‐dependent kinase messenger RNA (mRNA) and protein. Apoptosis was induced by blocking the expression of BCL‐2 and suppression of the Raf / ERK1 signaling pathways. These results indicated that MRBE may have the potential for treatment of human liver cancer, highlighting novel approaches for developing new pharmacological tools for the treatment of this deadly type cancer. Meanwhile, it provides a new direction for the medicinal added values of Chinese bayberry, which helped to broaden the diversified development of its industry chain. Abstract : The alcohol extracts of Chinese bayberry Myrica rubra branches (MRBE) effectively inhibited the proliferation of HepG2 cells by inducing cell cycle arrest in S phase and promoting apoptosis, with this arrest potentially mediated by the activation of p21–Cyclin–CDK (cyclin‐dependent kinase) complex signaling pathways. This study indicated that MRBE may have the potential for the treatment of human liver cancer.